An Experimental Study on the Reduction Kinetics of Iron Titanium Based Oxygen Carriers with CO Validated by First Principle Calculations. Issue 1 (9th January 2017) - Liu, Yu‐Cheng; Nachimuthu, Santhanamoorthi; Tsau, Kai‐Hao; Ku, Young; Jiang, Jyh‐Chiang
Abstract: Iron titanium based oxygen carriers are synthesized for chemical looping combustion process. The kinetics of reduction mechanism for three iron titanium based oxygen carriers with CO have been investigated using experimental and density functional theory (DFT) methods. Fe2 TiO5 shows higher reactivity towards CO than the others. The experimentally predicted activation energies are in good agreement with the DFT results. We have also investigated the formation of coke and our results clearly confirm that Boudouard reaction is responsible for the carbon generation at the end of the reduction mechanism. Further, the calculated carbon generation barriers are much higher than the reduction barrier, which indicate that we can control the operating temperature to avoid coke formation. Abstract : By using experimental and first principle methods, we report the reduction mechanism of three iron titanium based oxygen carriers, Fe2 TiO5, Fe2 TiO4 and FeTiO3 with CO for the chemical looping applications. The reduction of Fe2 TiO5 occurs much faster than that of Fe2 TiO4 and FeTiO3.